2015
DOI: 10.5194/acp-15-7571-2015
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the ratio of glyoxal to formaldehyde as an indicator of hydrocarbon precursor speciation

Abstract: The yield of formaldehyde (HCHO) and glyoxal (CHOCHO) from oxidation of volatile organic compounds (VOCs) depends on precursor VOC structure and the concentration of NO x (NO x = NO + NO 2 ). Previous work has proposed that the ratio of CHOCHO to HCHO (R GF ) can be used as an indicator of precursor VOC speciation, and absolute concentrations of the CHOCHO and HCHO as indicators of NO x . Because this metric is measurable by satellite, it is potentially useful on a global scale; however, absolute values and tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
74
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 50 publications
15
74
1
Order By: Relevance
“…Validation with aircraft data indicates that the OMI HCHO and NO 2 retrievals are accurate within 20 and 30 %, respectively (Lamsal et al, 2014;Zhu et al, 2016). CHOCHO/HCHO column ratios from OMI are consistent with aircraft observations (Kaiser et al, 2015), whereas previous SCIAMACHY retrievals showed large discrepancies (DiGangi et al, 2012).…”
Section: Methodssupporting
confidence: 57%
“…Validation with aircraft data indicates that the OMI HCHO and NO 2 retrievals are accurate within 20 and 30 %, respectively (Lamsal et al, 2014;Zhu et al, 2016). CHOCHO/HCHO column ratios from OMI are consistent with aircraft observations (Kaiser et al, 2015), whereas previous SCIAMACHY retrievals showed large discrepancies (DiGangi et al, 2012).…”
Section: Methodssupporting
confidence: 57%
“…However, the opposite behavior is observed in ground-based studies (DiGangi et al, 2012). Our recent CHOCHO retrieval from the OMI satellite instrument (Chan Miller et al, 2014) is in better agreement with surface observations of CHOCHO and R GF (Kaiser et al, 2015) compared to those from GOME-2 (Vrekoussis et al, 2010) and SCIAMACHY (Wittrock et al, 2006) as a result of improved background corrections and removal of NO 2 interferences. There remains the question of how observed CHOCHO-HCHO relationships are to be interpreted.…”
Section: Introductionsupporting
confidence: 64%
“…The CHOCHO observations in the free troposphere (> 3 km) have to be treated with caution since they are below the reported instrument precision (32 pptv, Kaiser et al, 2015). It is therefore difficult to determine whether the bias is due to a missing CHOCHO source in the model or instrument artifact.…”
Section: Constraints From Senex Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…TEMPO will resolve a wide range of NO x regimes due to its high spatial resolution, making NO 2 , H 2 CO and C 2 H 2 O 2 crucial datasets for validating isoprene chemistry. The ratio of C 2 H 2 O 2 to H 2 CO can provide insight on the VOC speciation and dominant chemical pathways in different locations [54]. Satellite C 2 H 2 O 2 retrievals are a good aromatic emissions constraint where these are high [15,68].…”
Section: Trace Gas Column Measurementsmentioning
confidence: 99%